Mental Size Scaling of Three-Dimensional Objects Perceived Visually or Tactilely - Szubielska, Magdalena (Adv Cogn Psychol, 2018)
The issue of pictorial or propositional nature of imagery remains unresolved. To take a step forward into the debate, we conducted a systematic evaluation of time and accuracy of mental scaling in sighted people. Participants viewed or touched three-dimensional objects and then had to imagine them in a resized version, depending on a given scale. Both the mental scaling time and the estimated object size were measured. To promote verbal or perceptual strategies, the size was estimated verbally or bimanually, respectively. It was found that time taken for mental scaling is a linear function of decreasing and increasing scale and that the modality of perception did not influence the time taken to perform the operation. The results contribute to the knowledge of object size estimation by revealing the interaction between the modality of the object perception and the accuracy of size estimation by sighted adults. The accuracy of estimation was greater when the imagery representation was based on visual rather than tactile perception, but only in the case of verbal size assessment. Verbal height estimation in centimeters showed a tendency towards underestimation, while bimanually estimated sizes tended to be overestimated. The results indicate that people can use pictorial as well as prepositional strategies, depending on the task.